Risk Assessment of Lead Exposure in The Oil Change Process with Dream Model - Chakim, Burhan Maritsal; Perdana, Moudy Putri; Ayuningtyas, Abir Reva; Ardianingsih, Ameylia Devi; Assidiq, Muhammad Raihan Aly; Fadil, Harisha (Universitas Negeri Semarang, 2025)
Lead (Pb) is an inorganic chemical element (95%) commonly found in soil, rocks, and plants. The use of fuel and oil containing lead is relatively high in Indonesia. Motorcycle or machine repair shop workers are at high risk of lead exposure, especially when removing used oil. Workers are exposed to oil containing lead while removing used oil from the engine, cleaning the engine cover with gasoline, opening the oil bottle cap, and pouring oil. Even, these processes can lead to lead poisoning. This study aims to evaluate workers’ risk of lead exposure during the oil-removing process at Repair Shop X. This descriptive study used a semi-quantitative approach with a Dermal Risk Exposure Method (DREAM). This study involved a total of 5 workers at Repair Shop X in the process of removing motorcycle oil. The actual dermal exposure value reached 340.36 based on the sum of the four activities. This was considered in the very high exposure category. Meanwhile, based on the activity obtained by calculating worker hygiene and work environment. The total exposure value was 306.33, which is a very high category. Therefore, using Personal Protective Equipment (PPE) such as gloves and maintaining worker and work environment hygiene by cleaning with water regularly can help minimize lead exposure.